Developing Interactive Learning with PowerPoint via the Canva Application" - Zebua, Warisman; Gulo, Sesiwarniwati; Bawamenewi, Arozatulo; Gulo, Misi Kristiani (Journal International Inspire Education Technology, 2024)
Research with the title "Development of Descriptive Text Learning Media with the Canva Application for Class X Students of SMK Negeri 1 Hiliduho". The problem of this research can be formulated, namely about how students use the Power Point application using the Canva application, as well as how attractive the Power Point learning media using the Canva application is for students, about the suitability of Power Point learning media for students and the effectiveness of Power Point learning media. . The aim of this research is to develop interactive learning with PowerPoint using the Canva application. This research uses a qualitative research method with a descriptive approach: the research subjects are students and teachers. The Research Object is the Development of Power Point Learning Media using the Canva Application, the Research Assessment Instrument is a Test Instrument, and an Assessment Rubric which consists of several assessment aspects, namely: appropriateness of material content, media display content, appropriateness of learning support processes, and appropriateness of material presentation. Method It collects data through observations and interviews to describe how students learn to write descriptive text with the help of the Canva application. The data analysis technique used in the research is firstly data reduction, secondly data presentation and thirdly drawing conclusions and identifying the suitability of the material as well as presenting the material using Power Point media, and describing the suitability of supporting the learning media used. The implementation of Canva media in Indonesian language learning went well, was conducive and interactive. Before entering the learning process, of course there are steps to make Canva media. In the implementation of the learning process there are several weaknesses that arise when learning takes place. However, the advantages of Canva's media implementation are more impactful than its weaknesses.